Will We Miss the Opportunity Again? - Oberbaum, Menachem (Homeopathy, 2020)
Coronavirus disease 2019 (COVID-19), caused by a new coronavirus, first appeared in late 2019. What initially seemed to be a mild influenza quickly revealed itself as a serious and highly contagious disease, and the planet was soon faced with a significant morbidity and mortality associated with this pathogen. For homeopathy, shunned during its 200 years of existence by conventional medicine, this outbreak is a key opportunity to show potentially the contribution it can make in treating COVID-19 patients. This should be done through performance of impeccably controlled, prospective, randomized clinical trials, with publication of their findings in well-ranked conventional medicine journals. If the homeopathy community fails to take advantage of this rare opportunity, it might wait another century for the next major pandemic.
Keywords: COVID-19; homeopathy; pandemics; randomized controlled trials